THE EFFECT OF GROSS DOMESTIC PRODUCT, INFLATION AND FOREIGN DIRECT INVESTMENT ON INEQUALITY IN INDONESIA - Sirait, Syamsinah; Japina, Henky; Simanjuntak, Helmina; Sinaga, Saria (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2025)
This study investigates the effects of Gross Domestic Product (GDP), inflation, and Foreign Direct Investment (FDI) on income inequality in Indonesia from 2010 to 2024, using the Gini ratio as a measure and employing multiple linear regression analysis on secondary data from the Indonesian Bureau of Statistics and Bank Indonesia. The findings reveal that GDP has a negative and statistically significant effect on inequality (p = 0.0424), suggesting that economic growth tends to narrow income disparities, whereas inflation exerts a positive and significant influence (p = 0.0326), indicating that higher inflation exacerbates unequal income distribution. Conversely, FDI was found to have no statistically significant impact (p = 0.3910). Together, these variables explain approximately 41% of the variation in inequality, highlighting the importance of pursuing inclusive growth strategies, effective inflation management, and enhancing the impact of foreign investment on income distribution. The policy implications underscore the need for government efforts to promote inclusive development, maintain price stability, and redesign FDI policies to contribute more directly to job creation and strengthening productive sectors